Hercules and the nine-headed Hydra - West, Tracey, 1965-; Holub, Joan; Williams, Suzanne, 1953- (Heroes in training., 2019)
When Hercules vandalizes Eurystheus' temple and Eurystheus threatens war with the Olympians, the Oracle Pythia decides that Hercules must present him with a scale from the nine-headed serpent, Hydra, to make amends.